Domestic wastewater sludge as a major substrate for cellulase production by two different fungal strains - Alam, Md. Zahangir; Drani, Afifah; Muyibi, Suleyman Aremu (2010)
A lab scale study was carried out to produce cellulase enzyme using two types of media: Media B consist of domestic wastewater sludge (DWS), microgranullar cellulose and oil palm empty fruit bunch (EFB) and Media M consist of DWS, microgranullar cellulose, oil palm EFB and addition of methanol. The 3% (v/v) inoculum of Trichoderma reesei Rut C-30 (ATCC 56765) and locally isolated Aspergillus spp. O-102A was inoculated to both media. The maximum total cellulase activity produced was 0.284 FPU/ml (Day 5) and endo-β-1,4 glucanase (CMCase) activity 2.631 IU/ml (Day 7) by T.reesei in media B. The cellulase of T.reesei was higher than O-102A, which only 0.093 FPU/ml (total cellulase activity) and 0.576 IU/ml (CMCase activity) produced by O-102A on the same day of fermentation in media B. The addition of methanol to the substrate (media M) was showing no positive effect to the production of cellulase enzyme for both strains.